1996
DOI: 10.1111/j.1468-1331.1996.tb00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Auditory event‐related potentials before and after treatment with nasal continuous positive airway pressure in sleep apnea syndrome

Abstract: Auditory event‐related potentials (ERP), multiple sleep latency tests, mini‐mental state exam, and depression tests were studied in 15 patients with obstructive sleep apnea syndrome (OSA). The P3 wave latency of ERP was significantly increased compared with 15 age‐matched control subjects. After 4 weeks and after 1 year of treatment of OSA by nasal continuous positive airway pressure (CPAP), there was no significant improvement in the abnormalities of ERP. These observed changes in ERP were not correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…In adults with OSA, evoked potential techniques have documented abnormal event‐related electrical activity that is consistent with PFC dysfunction (Kotterba et al. 1998; Neau et al. 1996; Sangal and Sangal 1997).…”
Section: The Model In Detailmentioning
confidence: 99%
“…In adults with OSA, evoked potential techniques have documented abnormal event‐related electrical activity that is consistent with PFC dysfunction (Kotterba et al. 1998; Neau et al. 1996; Sangal and Sangal 1997).…”
Section: The Model In Detailmentioning
confidence: 99%
“…Studies of auditory event-related potentials in patients with treated sleep apnea [37] found no improvement in abnormal P3 wave latencies, suggesting permanent structural changes in the white matter of the hemispheres, likely the result of ischemia. A subsequent study showed that healthy children with sleep-disordered breathing exhibit cerebral hemodynamic and neurobehavioral changes that are potentially reversible following adenotonsillectomy, indicating normalization of middle cerebral artery blood flow as measured with transcranial Doppler techniques [38].…”
Section: Cerebral Hemodynamic Changesmentioning
confidence: 94%
“…Intracranial hemodynamic changes occurring repeatedly may raise the risk of stroke and trigger irreversible ischemic changes in patients with poor hemodynamic reserve, particularly in borderzone areas and terminal artery territories. Preliminary studies of auditory event-related potentials in patients with sleep apnea [39] found no improvement in abnormal P3 wave latencies after treatment of sleep apnea, suggesting permanent structural changes in the white matter of the hemispheres, likely as a result of ischemia. Cerebral hemodynamic changes are of particular concern in patients with sleep apnea and intracranial arterial stenosis [40].…”
Section: Sleep Apnea and Cerebral Blood Flow Velocitymentioning
confidence: 96%